STUDIESON SODIUM SULPHIDE PREPAREDFROM SODIUM SULPHATE - Masood, Hajra; Khan, Lal (Biological Sciences - PJSIR, 2004)
The aim of this investigation was to prepare purified sodium sulphide which is utilized for multiple purposes. The reaction between commercial sodium sulphate and coal gives sodium sulphide and various products. The effect of reaction temperature and maximum composition were studied to establish the optimum conditions for maxium yield. The reaction is found suitable for large scale production of sodium sulphide from commercial sodium sulphate.